Challenges and interventions of school administrators in the retention of professional teachers in private schools - David, Elizabeth; Naparan, Genesis (Papanda Publishier, 2024)
This phenomenological qualitative study investigated the challenges and intervention strategies in the retention of teachers in private schools in Iligan City, Philippines. The researchers administered interviews to select private school administrators and teachers as the second data source. Three (3) significant themes were identified in strategies for retaining professional teachers: holistic teacher development, well-being and support, and nurturing a positive environment. Three (3) significant themes were derived from challenging experiences in keeping professional teachers: retention and turnover, mindset, and compensation. Four (4) significant themes were derived from the intervention strategies to retain professional teachers in private schools: supportive environment, innovative problem solving, empowerment, and professional and spiritual growth. It is recommended to administer tailored interventions, provide consistent leadership training, foster ongoing professional development, implement continuous strategy evaluation, and empower teachers through leadership skill development and grants for further studies to improve teacher retention in private schools.